Prevalence and Correlates of Mental Health Outcomes During the SARS-Cov-2 Epidemic in Mexico City and Their Association With Non-adherence to Stay-At-Home Directives, June 2020 - Mario H. Flores-Torres; Audrey R. Murchland; Priscilla Espinosa-Tamez; Jocelyn Jaen; Marion Brochier; Sergio Bautista-Arredondo; Héctor Lamadrid-Figueroa; Martin Lajous; Martin Lajous; Karestan Koenen (Frontiers Media S.A., 2021)
Objectives: To describe the prevalence and correlates of depressive symptoms, generalized anxiety disorder (GAD), and perceived negative mental health impact during the SARS-Cov-2 pandemic in Mexico City and evaluate their association with adherence to stay-at-home directives.Methods: Baseline data from a cohort study of 2,016 Mexico City government employees were analyzed using multivariable logistic regression models.Results: Among participants, 17.2% had clinically significant depressive symptoms, 21.6% had probable GAD, and 15.2% reported that the pandemic has had a major impact on their mental health. Factors including the presence of COVID-19 symptoms, self-isolation, and economic difficulties were associated with poor mental health. The presence of depressive symptoms and general anxiety were associated with non-adherence to public health directives, particularly among those who might have experienced these symptoms for the first time during the pandemic.Conclusion: Our study is one of the first to document the population mental health burden during the SARS-CoV-2 pandemic in Mexico and to provide evidence of the potential role of mental health in the adherence to public health measures.